DEVELOPMENT OF SOFTSKILL-BASED VIDEO GAME LEARNING MEDIA FOR MUFRᾹDAT MASTERY IN JUNIOR HIGH SCHOOL LEARNERS - Ramlan, Ramlan; Syahril, Sulthan; Kesuma, Guntur Cahaya; Erlina, Erlina; Aridan, Muhammad (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to determine the development process, feasibility, response, and effectiveness of soft skills-based video game learning media in mastering mufrodat. This research is a type of development research (R&D). By using the five steps of the ADDIE development model, namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The data collection techniques used were interviews, observations, questionnaires and tests. The research data were analyzed quantitatively and qualitatively. This research results in a soft skill-based video game Learning Media for mufrodat acquisition. Based on the validation that has been done by material and language experts, media experts and 8th-grade Arabic teachers, the average score is 4.63 with the category "very feasible". Based on the small group trial, the average score was 4.47, and in the large group, the average score was 4.61 with the interpretation of "very good" feasibility. In the pretest results of students' mastery of mufrodat, the average result was 42.44, and the average posttest score after using the developed media was 88.09. Thus, the soft skill-based video game learning media is feasible and effective for learning mufrodat of grade VIII students.